Inflammatory Myofibroblastic Tumor of the Nasal Septum - Yuri Okumura; Kazuhiro Nomura; Takeshi Oshima; Atsuko Kasajima; Takahiro Suzuki; Eichi Ishida; Toshimitsu Kobayashi (Case Reports in Otolaryngology)
We report an extremely rare case of inflammatory myofibroblastic tumor of the posterior edge of the nasal septum. An 11-year-old boy presented with frequent epistaxis and nasal obstruction persisting for one year. Based on the clinical presentation and imaging studies, juvenile angiofibroma was suspected, but angiography suggested the possibility of another type of tumor. Transnasal endoscopic surgery found that the tumor protruded into the nasopharynx from the posterior end of the nasal septum. Histological examination identified spindle cells with immunoreaction for vimentin, smooth muscle actin, and anaplastic lymphoma kinase (ALK), but not for desmin and cytokeratin. This is a report of inflammatory myofibroblastic tumor mimicking juvenile angiofibroma. This case suggests that angiography is helpful in the differential diagnosis of epipharyngeal tumor in adolescence.